SIMULTANEOUS BILATERAL ANTERIOR DISLOCATION OF THE SHOULDER WITH FRACTURES OF THE GREATER TUBEROSITY FOLLOWING TRAUMA- A CASE REPORT - Shetty, Sanath Kumar; Mathias, Lawrence J.; Rai, H. Ravindranath; Babu, P. Nirmal; R., Raj Sankar N.; C., Vinay Kumar (Journal of Health and Allied Sciences NU, 2014)
Simultaneous bilateral shoulder dislocations are usually posterior with anterior dislocations1 being rare and simultaneous anterior shoulder dislocations with fractures of the greater tuberosity5 being even more rare usually associated with trauma or seizures2,3 . Here we present a rare case of simultaneous bilateral anterior dislocation of the shoulder with fractures of the greater tuberosity following an unusual injury mechanism which was treated surgically.
Keywords: Bilateral; anterior dislocation; shoulder; fracture; greater tuberosity